How Emergency Nurses Develop Resilience in the Context of Workplace Violence: A Grounded Theory Study. Issue 5 (6th May 2021) - Han, Chin‐Yen; Chen, Li‐Chin; Lin, Chun‐Chih; Goopy, Suzanne; Lee, Hui‐Ling
Abstract: Purpose: To understand how emergency nurses develop resilience in the context of workplace violence. Design: This study employed grounded theory methodology. Thirty nurses from three hospital emergency departments in Taiwan were interviewed between August and December 2018. Methods: Semistructured interviews were used to collect data. Interviews were audio‐recorded and transcribed verbatim. Findings: The process through which emergency nurses who had experienced workplace violence developed resilience took place in three stages: the release of emotions after the assault; the interpretation of conflicting thoughts and actions; and the establishment of strategies to cope with workplace violence in the future. The core theme was the motivating role of professional commitment to emergency patient care. Conclusions: The results of this study can inform the development of support systems to enhance the resilience of nurses experiencing workplace violence by alerting healthcare administrators and governing institutions to their needs. Clinical Relevance: Emergency nurses viewed professional growth and professional commitment as an invisible motivator in the development of resilience following an encounter with workplace violence.